Diabetic nephropathy as risk factor associated with urinary tract infection, medical service of the hospital uldarico rocca fernandez, 2011 - 2015: Nefropatía diabética como factor de riesgo asociado a infección del tracto urinario, servicio de medicina del hospital uldarico rocca fernández, 2011 – 2015 - M., Martínez P. (2019)
Introduction: Diabetes mellitus is one of the most prevalent pathologies, affecting up to 9% of the world population until 2014 and in Peru, 4.3% of the adult population is already diabetic. These patients are more susceptible to infectious diseases, being the urinary tract the most frequent, considering complicated, which means that they must receive hospital management, leading to a decrease in their quality of life. Objective: To determine if diabetic nephropathy is a risk factor for the prevalence of urinary tract infection in patients hospitalized in the Uldarico Hospital medical service Rocca Fernández Methods: It is an observational, analytical study of longitudinal section, case and control type; the information was collected through a data sheet using the medical records of the patients hospitalized in the service of medicine of the Uldarico Rocca Fernández Hospital in the 2011-2015 period. The sample was obtained by probabilistic sampling, being the size of this 360, with a proportion of cases and controls 1: 1. Results: The diabetic nephropathy obtained an OR = 8.62 (IC95% 4.78 - 15.57), the macroalbuminuria obtained an OR = 5.75 (IC95% 2.99 - 11.06), the alkaline pH obtained an OR = 5.42 (IC95% 3.22 - 9.13) and the glycemic control obtained an OR = 5.44 (IC95% 3.44 - 8.88). Conclusion: Diabetic nephropathy is associated with a higher prevalence of UTI in patients hospitalized in the medicine service of the Ulda Rocca Fernández Hospital.   DOI:  10.25176/RFMH.v19.n1.1791